Makuha ka sa galaw galaw sa pakikipag-usap ng mga Pilipinong kolehiyolo at kolehiyalang naninirahan sa Metro Manila - Virgino, Ayla Christadel S.,eauthor; Tanedo, Jose Alberto (Quezon City College of Fine Arts, University of the Philippines Diliman, 2016)
Nonverbal communication reflects the emotions of a person behaving. It allows the actual manifestation of his or her state of mind. In able to further understand as to why this nonverbal communication processes take place, some researches valued the environmental and social stimuli as much as the bodily gestures themselves. It is heavily reinforced by social conventions and bounded by cultural underpinnings. Thus, a great deal of nonverbal communication is an interplay on socialization and culture that reveals identity. May it be from an individualistic persona to a wider collective sense. This study aims to investigate and explore Philippine culture through a different lens. Philippine nonverbal communication is a fresh scope of knowledge that is relatively untouched and undocumented formally, which is why the researcher of this thesis is compelled to shed light to its roles, contributions and importance as a microelement of Philippine culture. To attain this, the researcher sees the use of an interactive mobile application as a befitting medium to achieve the objectives of the study as it shows on her research and data analysis results. The interactive mobile application, which followed the research, cultivates an environment where the user works his or her way around college life in Metro Manila, a life chapter that primes a person to the bigger world ahead. It is a collection of interconnected narratives that informs its intended audience about the topic through an efficient user interface design that aims to cater information by utilizing interactivity and entertainment as means to amplify empathy.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leave 172.
Keywords: Nonverbal communication -- Philippines; Body language -- Philippines; Mobile apps